Enhancing EFL Reading Proficiency through Authentic Assessment: A Case Study on Student Engagement and Learning Behavior - Ardianti, Triubaida Maya (Universitas Muhammadiyah Mataram, 2024)
Authentic assessment includes alternative assessments that engage students through authentic tasks with authentic materials. It includes performance assessment, portfolio, self-assessment, etc. These types of assessment may help teacher to monitor students’ learning progress and attitudes. In response to that, the present study aimed to discover students’ responses regarding the application of authentic assessment to help them read longer English texts. To achieve the purpose of the study, a case study was employed. Data were gathered from 16 week-observation, students’ work, and forms of students’ self-assessment. The results of the study revealed that despite a shift on the students’ motivation and learning behavior, a positive trend was indicated. At the beginning, students tended to show anxiety and hesitance when expressing their interpretation of reading text during in-class discussions. Throughout the time, they gradually invested more efforts, specifically in demonstrating their thoughts of reading materials. Additionally, the number of students actively delivering opinions were increasing.